Training on Making Simple Financial Statements for Youth in kecamatan Lubuk Alung as an Effort to Equip Entrepreneurial Skills and Strengthening of UMKM - Ravelby, Thesa Alif; Nurofik, Agus; Trismiyanti, Dessy (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
Para pemuda yang di Kecamatan Lubuk Alung tergolong para pemuda aktif yang beberapa diantaranya berinisiatif berwirausaha skala mikro. Semangat para pemuda berwirausaha ditindaklanjuti oleh tim Pengabdian Kepada Masyarakat STIE Perdagangan dengan membantu mereka mengatasi beberapa persoalan yang umumnya dialami oleh usaha khususnya di bidang laporan keuangan. Oleh sebab itulah pengabdian masyarakat ini dilaksanakan dengan tujuan membantu unruk memulai usaha dalam pencatatan keuangan yang rapi dan benar melalui penyampaian ilmu dasar-dasar keuangan. Metode yang dipilih dengan cara memberikan penyuluhan dan pelatihan. Hasil dari kegiatan pengabdian masyarakat ini adalah panduan praktis dan sederhana berupa pedoman bagi usaha mikro dalam membuat laporan keuangan sederhana yang di aplikasi dengan microsoft excel yang terangkum dalam bentuk materi PKM STIE Perdagangan. Training on Making Simple Financial Statements for Youth in kecamatan Lubuk Alung as an Effort to Equip Entrepreneurial Skills and Strengthening of UMKM Abstract: The youths in Kecamatan Lubuk Alung are classified as active youths, some of whom have initiated micro-scale entrepreneurship. The spirit of entrepreneurial youth was followed up by the Community Service team of STIE Perdagangan by helping them overcome some of the problems commonly experienced by businesses, especially in the field of financial reporting. That is why this community service is carried out with the aim of helping to start a business in recording neat and correct financials through the delivery of basic financial knowledge. The method chosen is by providing counseling and training. The results of this community service activity are practical and simple guidelines in the form of guidelines for micro businesses in making simple financial reports that are applied with Microsoft Excel, which are summarized in the form of PKM STIE Perdagangan. Keywords: Community Services, Financial Statements, Micro Business.